Sensitivity And Specificity Of Crandal And Ilayperuma’s Formula To Predict Adult Weight And Height - Wardah; Kharisna, Dendy; Febtrina, Rizka (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Many medical conditions do not allow direct weighing or measurement of body height. Thecircumference of the upper arm (CUA) is an alternative in determining body weight, while the ulna lengthcan be used as an alternative for height. The aim of this study was to identify the sensitivity and specificityof Crandal and Ilayperuma’s Formula to predict adult weight and height in Indonesia, especially inPekanbaru. This study conducted using a quantitative approach with cross sectional design and involving116 respondents who recruited using accidental sampling. The instrument used is a questionnaire, manualweight scales, metlin, and heel microtoise. Data were analyzed using spearman to aand logistic regressiontest. The results showed that the sensitivity value of the Crandal and Ilayperuma’s formula were 78,2% and63,4%. Meanwhile, the specificity value of Crandal and Ilayperuma’s formula were 75,4% and 80%. TheArea Under the Curve (AUC) values in the Crandal and Ilayperuma formulas were 76,7% and 70,7%. Basedon these findings, it can be concluded that the Crandal and Ilayperuma’s formula can be used as analternative in determining the estimation of weight and height of adults in Indonesia, even with moderatediagnostic power.